Effect of Orally Administered Cisapride, Bethanechol, and Erythromycin on the Apparent Efficiency of Colostral IgG Absorption in Neonatal Holstein‐Friesian Calves. (31st January 2015) - Ghoreishi, S.M.; Nouri, M.; Rasooli, A.; Ghorbanpour, M.; Mokhber‐Dezfouli, M.R.; Constable, P.D.
Abstract : Objective: To evaluate the effect of orally administered cisapride, bethanechol, and erythromycin on the absorption of colostral IgG in dairy calves. Animals: Twenty‐four healthy neonatal Holstein‐Friesian calves. Procedures: Calves were randomly assigned to one of the following treatments: 0.9% NaCl solution (2 mL, PO; negative control); erythromycin lactobionate (20 mg/kg BW, PO; anticipated to be a positive control); cisapride (0.5 mg/kg BW, PO); bethanechol chloride (0.5 mg/kg BW, PO). Calves were fed 3 L of pooled bovine colostrum containing acetaminophen (50 mg/kg) by suckling and oroesophageal intubation 30 minutes after each treatment was administered. Jugular venous blood samples were obtained periodically after the start of feeding and plasma total IgG, protein, acetaminophen, and glucose concentrations determined. Abomasal emptying rate was assessed by the time to maximal plasma acetaminophen concentration. Results: Oral administration of cisapride facilitated the absorption of colostral IgG and protein. The effect of cisapride on abomasal emptying rate could not be evaluated because cisapride appeared to interfere with acetaminophen metabolism. Based on the total IgG and total protein concentration‐time relationships, the beneficial effects of cisapride appeared to occur early after oral administration and were transient. Conclusions and Clinical Importance: Additional studies appear indicated to characterize the effect of cisapride dose on the magnitude and duration of its effect on facilitating the absorption of colostral IgG and protein. Identification of a nonantimicrobial method for increasing abomasal emptying rate, such as cisapride, will potentially provide a practical and effective method for facilitating transfer of passive immunity in colostrum‐fed dairy calves.